Review of Judgments under the Ethiopian Civil Procedure Code: Where Should Litigation Stop? - Dessalegn, Beza (Bahir Dar University Journal of Law, 2022)
Review of judgments in civil litigation offers litigants a chance to have theircases re-examined either by the court of rendition or by a court found at a higherhierarchy than the court which rendered the judgment firsthand. Thisundertaking tries to strike a delicate balance between the search for truth andthe need to bring litigation to an end. In engaging in any kind of interpretationconcerning the review of judgments, courts are required to balance these competinginterests. This article is a critical examination of the law on review of judgmentsagainst the various interpretations of the Cassation Division. Although theCassation Division offers a novel approach in its efforts to bring consistency toour legal system, it has however overstepped its authority from a lawinterpreting organ to one of a law-making body in the binding interpretation itgave on review of judgments based on newly discovered evidence.